Health Risk in Hot Springs: A Literature Review - Chaterine Rahel; Retno Adriyani; Hernanda Arie Nurfitria (Journal of Health Science and Prevention, 2021)
Natural hot spring is one of the recreational water. The public used it for recreation, relaxation, and therapy. The water quality should meet standards, such as free from microorganisms to prevent the onset of health complaints. This paper aimed to identify the pathogenic microorganisms and recreational water illness in natural hot spring users from worldwide studies. Method: This systematic review analysis use PRISMA Protocol as a guide to provide this article and PEO Framework to specified the criteria. Various database used to find those article is NCBI, Google Scholar, and Science Direct. In total of 10 eligible articles to analyse from 2010 -2020. Discussion: The result showed that hot spring users experienced health complaints after using hot springs contaminated with pathogenic microorganisms. The microorganisms identified were Naegleria spp, Naegleria fowleri, Legionella pneumophila, Vittaforma corneae, Mycobacterium avium-intracellulare Complex (MAC), Pseudomonas aeruginosa, and Mycobacterium phocaicum. Recreation water illnesses identified were Primary Amebic Meningoencephalitis (PAM), Legionella pneumonia, Pseudomonas foliculitis, Pseudomonas mastitis, Microsporidial keratitis, Hot tub lung (HTL), and P. aeruginosa pneumonia. Besides the water quality, age, comorbid, and frequency of visiting hot springs were risk factors of recreational water illness. Conclusion: The onset of recreational water illness in users of hot springs was influenced by the quality of water microbiology and age.